Respon Pertumbuhan dan Komposisi Isoprenoid Semai Acanthus ilicifolius Linn - Abu Hayullah; Mohammad Basyuni; Lollie Agustina (Peronema Forestry Science Journal, 2012)
The purpose of this study is to analyze growth of A. ilicifolius seedling in response to salinities and its isoprenoid composition. The mangrove seedling were grown under different salinities for 5 mounth. The maximum growth of A. ilicifolius seedlings was in 0.5 % salinity and this elevation appeared to be attenuated by increasing of salinity. The results showed the composition of the isoprenoid in  A.ilicifolius  were consist of four phytosterols namely stigmasterol, campesterol, β-sitosterol, cycloartenol, and six triterpenoids : taraxerol, β-amyrin, germanicol, betulin, α-amyrin and lupeol. This research may provide information the characterization of triterpenoid and phytosterol of A. ilicfolius seedlings. Keywords : Mangrove, A.ilicifolius Linn, isoprenoid, and Salinity